2018
DOI: 10.1038/s41467-018-05890-2
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of MHC region in lung cancer highlights independent susceptibility loci by ethnicity

Abstract: The basis for associations between lung cancer and major histocompatibility complex genes is not completely understood. Here the authors further consider genetic variation within the MHC region in lung cancer patients and identify independent associations within HLA genes that explain MHC lung cancer associations in Europeans and Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…The HLA region is critical for innate and adaptive immune response and has a complex relationship with cancer risk. Heterogeneous associations with HLA haplotypes have been reported for different subtypes of NHL 44 and lung cancer 45 , suggesting that relevant risk variants are likely to differ within, as well as between, cancers. Studies have further demonstrated that somatic mutation profiles are associated with HLA class I (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA region is critical for innate and adaptive immune response and has a complex relationship with cancer risk. Heterogeneous associations with HLA haplotypes have been reported for different subtypes of NHL 44 and lung cancer 45 , suggesting that relevant risk variants are likely to differ within, as well as between, cancers. Studies have further demonstrated that somatic mutation profiles are associated with HLA class I (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, HLA-A * 01, HLA-C * 05, and HLA-C * 07 have been shown to be positively associated with survival of melanoma patients (Paschen et al, 2005;Campillo et al, 2006;Zhu et al, 2012), whereas HLA-B * 14, HLA-A * 24, HLA-A * 31, HLA-C * 14, and HLA-B * 13 are negatively associated with survival of melanoma patients (Marincola et al, 1995;Kawakami et al, 2000;Akiyama et al, 2005;Kandilarova et al, 2016;Rogel et al, 2019). Apart from these, HLA-DRB1 * 07 has been shown to be negatively associated with patient survival in other cancers such as lung cancer, cervical cancer, and breast cancer (Ferreiro-Iglesias et al, 2018;Hu et al, 2018;Spraggs et al, 2018). Further, in the current study, a parameter RS was computed to evaluate the cumulative effect of the presence of SF and SU superalleles in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA region is critical for innate and adaptive immune response and has a complex relationship with cancer risk. Heterogeneous associations with HLA haplotypes have been reported for different subtypes of NHL 50 and lung cancer, 51 suggesting that relevant risk variants are likely to differ within, as well as between, cancers. Studies have further demonstrated that somatic mutation profiles are associated with HLA class I 52 and class II alleles.…”
Section: Discussionmentioning
confidence: 99%